Direct Ink Writing of Highly Conductive MXene Frames for Tunable Electromagnetic Interference Shielding and Electromagnetic Wave-Induced Thermochromism - Wu, Xinyu; Tu, Tingxiang; Dai, Yang; Tang, Pingping; Zhang, Yu; Deng, Zhiming; Li, Lulu; Zhang, Hao‑Bin; Yu, Zhong‑Zhen (Nano-Micro Letters, 2021)
The highly integrated and miniaturized next-generation electronic products call for high-performance electromagnetic interference (EMI) shielding materials to assure the normal operation of their closely assembled components. However, the most current techniques are not adequate for the fabrication of shielding materials with programmable structure and controllable shielding efficiency. Herein, we demonstrate the direct ink writing of robust and highly conductive Ti3C2Tx MXene frames with customizable structures by using MXene/AlOOH inks for tunable EMI shielding and electromagnetic wave-induced thermochromism applications. The as-printed frames are reinforced by immersing in AlCl3/HCl solution to remove the electrically insulating AlOOH nanoparticles, as well as cross-link the MXene sheets and fuse the filament interfaces with aluminum ions. After freeze-drying, the resultant robust and porous MXene frames exhibit tunable EMI shielding efficiencies in the range of 25–80 dB with the highest electrical conductivity of 5323 S m−1. Furthermore, an electromagnetic wave-induced thermochromic MXene pattern is assembled by coating and curing with thermochromic polydimethylsiloxane on a printed MXene pattern, and its color can be changed from blue to red under the high-intensity electromagnetic irradiation. This work demonstrates a direct ink printing of customizable EMI frames and patterns for tuning EMI shielding efficiency and visualizing electromagnetic waves. Highlights: 1 3D printing of MXene frames with tunable electromagnetic interference shielding efficiency is demonstrated. 2 Highly conductive MXene frames are reinforced by cross-linking with aluminum ions. 3 Electromagnetic wave is visualized by electromagnetic-thermochromic MXene patterns.